Optimal cutoff scores of the Chinese version of 15-item negative symptom assessment that indicate prominent negative symptoms of schizophrenia - Zhou, Qi; Pu, Cheng-cheng; Huang, Bing-jie; Miao, Qi; Zhou, Tian-hang; Cheng, Zhang; Gao, Tian-Qi; Shi, Chuan; Yu, Xin (Frontiers in Psychiatry, 2023)
Objective: The Chinese version of 15-item Negative Symptom Assessment (NSA-15) is an instrument with a three-factor structure specifically validated for assessing negative symptoms of schizophrenia. To provide a reference for future practical applications in the recognition of schizophrenia patients with negative symptoms, this study aimed to determine an appropriate NSA-15 cutoff score regarding negative symptoms to identify prominent negative symptoms (PNS). Methods: A total of 199 participants with schizophrenia were recruited and divided into the PNS group (n=79) and non-PNS group (n=120) according to Scale for Assessment of Negative Symptoms (SANS) scores. Receiver-operating characteristic (ROC) curve analysis was used to determine the optimal NSA-15 cutoff score for identifying PNS. Results: The optimal cutoff NSA-15 score for identifying PNS was 40. Communication, emotion and motivation factors in the NSA-15 had cutoffs of 13, 6 and 16, respectively. The communication factor score had slightly better discrimination than scores on the other two factors. The discriminant ability of the global rating of the NSA-15 was not as good as that of the NSA-15 total score (area under the curve (AUC): 0.873 vs. 0.944). Conclusion: The optimal NSA-15 cutoff scores for identifying PNS in schizophrenia were determined in this study. The NSA-15 provides a convenient and easy-to-use assessment for identifying patients with PNS in Chinese clinical situations. The communication factor of the NSA-15 also had excellent discrimination.